What to do about Alice? : how Alice Roosevelt broke the rules, charmed the world, and drove her father Teddy crazy! - Kerley, Barbara; Fotheringham, Edwin (New York : Scholastic Press, 2008)
A brief biography in pictures and simple text of Alice Roosevelt, the daughter of Theodore Roosevelt and his first wife.
Young Alice Lee Roosevelt made a name for herself in the White House through her many unconventional and amusing activities while living there with her family and president father.
Keywords: Longworth, Alice Roosevelt, -- 1884-1980 -- Juvenile literature; Roosevelt, Theodore, -- 1858-1919 -- Family -- Juvenile literature; Longworth, Alice Roosevelt, -- 1884-1980; Roosevelt, Theodore, -- 1858-1919 -- Family; Longworth, Alice Roosevelt, -- 1884-1980; Roosevelt, Theodore, -- 1858-1919 -- Family; Children of presidents -- United States -- Biography -- Juvenile literature; Legislators' spouses -- United States -- Biography -- Juvenile literature; Children of presidents; Legislators' spouses; Presidents -- United States -- Children -- Biography; Women -- Biography